PERLINDUNGAN HUKUM BAGI KONSUMEN AKIBAT PERIKLANAN PRODUK KOSMETIK - Resti Riancana,; Nur Moh. Kasim,; Wantu, Fence M. (The Juris, 2023)
This article aims to determine consumer protection due to misleading cosmetic product advertisements also about influencer liability due to advertising cosmetic products that do not match the truth. The method in this study is a normative legal research method, with legal and a conceptual approach. The analysis technique is qualitative analysis technique by reviewing laws and regulations and analyzing them. The result of this study is that the state has regulated consumer protection in terms of misleading cosmetic advertisements, but the position of influencers has not been clearly regulated in Indonesian law. So in demanding accountability and to protect consumer rights, the rules are still unclear.